Comparison of the Microstructures and Properties of Different Microcannulas for Hyaluronic Acid Injection. Issue 2 (August 2018) - Wu, Kelun; Xie, Li; Wang, Muyao; Jiang, Yichen; Tang, Yingfeng; Wang, Hang
Abstract : Background: Microcannulas are used for hyaluronic acid and other filler injections and reduce the side effects and complications. There are several microcannulas and the differences between microcannulas have not been carefully investigated. The purpose of this study was to compare the microstructures and properties of different microcannulas by several trials and provide guidance for clinical application. Methods: Nine types of microcannulas from different manufacturers were chosen. Scanning electron microscopy was used to obtain high-definition images of microstructures, chemical composition analyzers were used to test the chemical composition of the tips, and a universal testing machine was used to measure mechanical properties. The injection speed test recorded the time spent for the weight to push hyaluronic acid out of microcannulas. The vessel piercing force test was conducted to simulate the process of puncturing the vessels in vitro. Results: The scanning electron microscopic images showed the tip shapes and inner surfaces that may relate to the characteristics. The chemical composition of most microcannulas met the American Society for Testing and Materials standards basically. The mechanical properties were obviously different. The results of the injection speed test were discrepant more than seven times. The vessel piercing test showed which microcannula was the most difficult and easiest to puncture the aorta. Conclusions: The results indicated that there are significant differences between different microcannulas. The differences are instructive to physicians for selecting suitable microcannulas to improve the injection effect and reduce discomfort and complications. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, V.